2001
DOI: 10.5194/angeo-19-925-2001
|View full text |Cite
|
Sign up to set email alerts
|

Typhoon 9707 observations with the MU radar and L-band boundary layer radar

Abstract: Abstract. Typhoon 9707 (Opal) was observed with the VHF-band Middle and Upper atmosphere (MU) radar, an L-band boundary layer radar (BLR), and a vertical-pointing C-band meteorological radar at the Shigaraki MU Observatory in Shiga prefecture, Japan on 20 June 1997. The typhoon center passed about 80 km southeast from the radar site. Mesoscale precipitating clouds developed due to warmmoist airmass transport from the typhoon, and passed over the MU radar site with easterly or southeasterly winds. We primarily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…Similar features of radial wind were found in Fig. 7, and also reported by Jorgensen (1984a), Tabata et al (1992), Teshiba et al (2001), and Shibagaki et al (2003). Cyclonic winds gradually became stronger in time over both stations, and, in particular, the horizontal gradient of the cyclonic wind was large in the main rainbands, that is the rainbands were developed where the horizontal shear of the cyclonic wind was strong.…”
Section: Characteristics Of Storm-relative Wind Behaviorsupporting
confidence: 70%
“…Similar features of radial wind were found in Fig. 7, and also reported by Jorgensen (1984a), Tabata et al (1992), Teshiba et al (2001), and Shibagaki et al (2003). Cyclonic winds gradually became stronger in time over both stations, and, in particular, the horizontal gradient of the cyclonic wind was large in the main rainbands, that is the rainbands were developed where the horizontal shear of the cyclonic wind was strong.…”
Section: Characteristics Of Storm-relative Wind Behaviorsupporting
confidence: 70%
“…Detailed kinematic structures within and around rainbands have been clarified in the VHF-band radar observation (May 1996;May et al 1994;Teshiba et al 2001). In this study, we successfully observed Typhoon 9426 (Orchid) by the MU (middle and upper atmosphere) radar of the VHF band at Shigaraki, Shiga, Japan (136.10 E, 34.85 N) on 29-30 September 1994, the center of which almost passed over the radar site.…”
Section: Introductionmentioning
confidence: 82%
“…In rainy conditions, the observation altitude of BLR increases up to 10 km (Teshiba et al 2001). Time and height resolutions are 60 s and 150 m. Reflectivity observed by BLR is also employed to investigate the vertical structure of precipitation systems.…”
Section: Upper Sounding Observationsmentioning
confidence: 99%